Postburn breast reconstruction: a scoping review - Eduardo Gus; Jane Zhu; Stephanie G Brooks (SAGE Publishing, 2023)
Introduction Postburn breast deformities pose functional and aesthetic concerns for burn patients, particularly when injury occurs before puberty, as normal breast development may be hindered. Postburn breast reconstruction aims at restoration of native anatomic features, as well as re-establishment of symmetry. The objectives of this scoping review are to map the literature on scar management and breast reconstruction, highlighting strategies that are particular to postburn deformities, as well as to establish optimal timing principles. Methods A comprehensive search of the English literature across MEDLINE and EMBASE databases, including the grey literature, was conducted. Literature of all study designs were eligible, provided it discussed the treatment of postburn breast deformities. Results A total of 64 studies were included. The most common study design was case series (58%) followed by retrospective cohorts (28%). Scar contracture release with split thickness skin grafts (26%) and various techniques for nipple-areola reconstruction (22%) were the most common reconstructive procedures. Discussion Scar contracture releases predominate when there is normal breast development under a contracted skin envelope, and should be performed as soon as breast mound development is restricted. Surgical techniques widely used for postmastectomy reconstruction are required for patients with amastia or hypoplastic breasts. Conclusion Given the heterogeneity of defects, availability of donor sites, and patient preference, no standardized guideline is available. Surgeons should combine basic scar management principles with postmastectomy techniques, adapting the surgical approach to features that are particular to thermally injured patients, as well as taking into account ideal timing considerations. Lay Summary Breast deformities secondary to burn scars pose functional and aesthetic concerns for burn patients, particularly when injury occurs before puberty, as normal breast development may be hindered. Postburn breast reconstruction aims at restoration of native anatomic features, as well as re-establishment of symmetry. This literature review aimed at summarizing the available techniques to treat postburn breast deformities, as well as establishing optimal timing guidelines, given these issues may occur at any phase of breast development. When there is breast development under a scarred skin envelope, treatment entails scar contracture release and should be recommended as soon as the diagnosis is established, in order to allow the breast to further develop in an unrestricted manner. When there is absence of breast tissue, surgical techniques widely utilized for breast cancer reconstruction are warranted, and should be delayed until no further breast development is expected. Given the heterogeneity of deformities, availability of donor sites, and patience preference, no standardized guideline is available. Treatment options include several surgical techniques, in addition to non-surgical scar management, and timing considerations must take into account the patient's developmental phase and psychosocial wellness.